STUDI TENTANG KEPEDULIAN ORANG TUA DALAM MELANJUTKAN PENDIDIKAN ANAK KE SMA DAN SEDERAJAT DI KENAGARIAN GAUANG KECAMATAN KUBUNG KABUPATEN SOLOK - Afrisandra, Afrisandra; Suarto, Edi; Nefilinda, Nefilinda (Pendidikan Geografi, 2013)
This study aimed to obtain the data, process, analyze and discuss the concerns of parents in continuing education to school children and equal in Kenagarian Gauang Solok District lemur views of: 1) Income of parents, 2) Expended time parents, and 3) facilities. This study considered the descriptive research. Population of this research is all the parents who have a child and went on to high school education and equal. Respondent sampling done with total sampling technique, which amounted to 56 respondents. The research data was collected through questionnaires. Data were analyzed using descriptive analysis techniques and the percentage formula. The results of this study as follows: 1) The median income parents in Kenagarian Gauang Solok District lemur is between Rp 1,000,000 - Rp 1,900,000 in one month (48.21%). Workers are essentially farming (53.57%), parents in general currently do not have a second job (73.21%), but there are some parents who have a second job as a merchant, farmer, a motorcycle / labor and farming. Income earned from side jobs uncertain, 2) parents less time to guide the children (62.5%). In one day the parents only have 1 hour to guide the child at home (55.36%), because parents are busy with work (57.14%) so it is not uncommon for people aged less attention to teaching children (67.86%), 3) the main facilities needed to continue the childs education is reading books (73.21%) but the facilities are not adequate owned subsidiary (60.71%) because parents are less concerned with children learning facilities (58.93%) and less attention to childrens learning tool (66.07%). Parents should further increase the revenue, taking time for children and Â provide fasilatas adequate to support the childs learning process.